Minat Para Siswa Madrasah Aliyah dan Faktor-Faktor yang. Mempengaruhi Mereka Lanjut Studi ke Perguruan. Tinggi Keagamaan Islam - Zainab Hartati; Nurul Wahdah; Jasiah Jasiah; Abdul Qodir; Emawati Emawati; Akhmad Sairaji; Pithriani Pithriani (JURKAM: Jurnal Konseling Andi Matappa, 2021)
The present survey study investigates Madrasah Aliyah students' interests in continuing their studies to the Islamic Religious Colleges and the factors that influence them. The participants were 177(one hundred and seventy-seven) students of Class XII from Madrasah Aliyah and Islamic Boarding Schools in Palangka Raya City. Data were obtained by distributing the questionnaires consisting of the participants’ demographic information and the questions related to interests. Data were analysed through descriptive statistics. The results of the study showed that: 1) the students who are interested in continuing their study to higher education institutions are 43.5% out of all participants, the others do not have a plan and decide not to continue their studies because of the low economic backgrounds of their parents who work as construction labourers, small traders, laundry workers, and other jobs. 2) the factors that influence interest in registering at IAIN Palangka Raya are the parents, students’ desires, peers, and family economic status. 3) IAIN Palangka Raya occupies the top position known to students in Madrasah Aliyah in Palangka Raya City.  The most dominant sources of information on the existence of IAIN Palangka Raya as one of the Islamic Religious College are from their friends, and others are from their families, neighbours, brochures, social media, schools, and teachers.